No evidence for an increase in circulatory disease mortality in astronauts following space radiation exposures. (August 2016) - Cucinotta, Francis A.; Hamada, Nobuyuki; Little, Mark P.
Abstract: Previous analysis has shown that astronauts have a significantly lower standardized mortality ratio for circulatory disease mortality compared to the U.S. population, which is consistent with the rigorous selection process and healthy lifestyles of astronauts, and modest space radiation exposures from past space missions. However, a recent report by Delp et al. estimated the proportional mortality ratio for ages of 55–64 y of Apollo lunar mission astronauts to claim a high risk of cardiovascular disease due to space radiation compared to the U.S. population or to non-flight astronauts. In this Commentary we discuss important deficiencies in the methods and assumptions on radiation exposures used by Delp et al. that we judge cast serious doubt on their conclusions.